Answer:
The number 3 makes this statement true.
![x=3](https://tex.z-dn.net/?f=x%3D3)
Step-by-step explanation:
Given the equation:
![(12*3)*6=12*(x*6)](https://tex.z-dn.net/?f=%2812%2A3%29%2A6%3D12%2A%28x%2A6%29)
Using the order of operations, we can evaluate the terms in the parentheses through the process of multiplication:
![36*6=12*6x](https://tex.z-dn.net/?f=36%2A6%3D12%2A6x)
Multiply the terms on both sides of the equation:
![216=72x](https://tex.z-dn.net/?f=216%3D72x)
Finally, divide both sides of the equation by the coefficient of
, which is
:
![3=x](https://tex.z-dn.net/?f=3%3Dx)
![x=3](https://tex.z-dn.net/?f=x%3D3)
-
Let's check our work by substituting the solved
value for
![(12*3)*6=12*(3*6)](https://tex.z-dn.net/?f=%2812%2A3%29%2A6%3D12%2A%283%2A6%29)
![36*6=12*18](https://tex.z-dn.net/?f=36%2A6%3D12%2A18)
![216=216](https://tex.z-dn.net/?f=216%3D216)
Since both sides of the equation are equal to each other, our solution is correct!